Interactive 3D segmentation repair with image-foresting transform, supervoxels and seed robustness - Tavares, Anderson Carlos Moreira (2017)
Image segmentation consists on its partition into relevant regions, such as to isolate the pixels belonging to desired objects in the image domain, which is an important step for computer vision, medical image processing, and other applications. Many times automatic segmentation generates results with imperfections. The user can correct them by editing manually, interactively or can simply discard the segmentation and try to automatically generate another result by a different method. Interactive methods combine benefits from manual and automatic ones, reducing user effort and using its high-level knowledge. In seed-based methods, to continue or repair a prior segmentation (presegmentation), avoiding the user to start from scratch, it is necessary to solve the Reverse Interactive Segmentation Problem (RISP), that is, how to automatically estimate the seeds that would generate it. In order to achieve this goal, we first divide the segmented object into its composing cores. Inside a core, two seeds separately always produce the same result, making one redundant. With this, only one seed per core is required. Cores leading to segmentations which are contained in the result of other cores are redundant and can also be discarded, further reducing the seed set, a process called Redundancy Analysis. A minimal set of seeds for presegmentation is generated and the problem of interactive repair can be solved by adding new seeds or removing seeds. Within the framework of the Image-Foresting Transform (IFT), new methods such as Oriented Image-Foresting Transform (OIFT) and Oriented Relative Fuzzy Connectedness (ORFC) were developed. However, there were no known algorithms for computing the core of these methods. This work develops such algorithms, with proof of correctness. The cores also give an indication of the degree of robustness of the methods on the positioning of the seeds. Therefore, a hybrid method that combines GraphCut and the ORFC cores, as well as the Robustness Coefficient (RC), have been developed. In this work, we present another developed solution to repair segmentations, which is based on IFT-SLIC, originally used to generate supervoxels. Experimental results analyze, compare and demonstrate the potential of these solutions.